Salsabila Bakery Shop / Daeng Kasturi Nazman - Nazman, Daeng Kasturi (2020)
As a student of Fundamental of Entrepreneurship (ENT300), the student needs to carry out a Case study in order to fulfil the subject as stated. During a case study, this student needs collect all information about a company to complete study case, so this student decides to face-to-face interview the owner of Salsabila Bakery Shop, who name is Puan Najibah Binti Mohamed Zaid. As the result of interview to the owner, this student has known about their background of the business, organizational structure, type of business model, products or services marketing and operational strategy. This student also able to analyse the business entity using SWOT through case study and identify the problem faced by this company and trying to recommend an alternative solution towards the problem.